A microstructures generation tool for virtual ply property screening of hybrid composites with high volume fractions of non-circular fibers – VIPER. (February 2020) - Herráez, M.; Segurado, J.; González, C.; Lopes, C.S.
Abstract: Within the framework of computational micromechanics (CMM), a simulation toolset is being developed to predict the mechanical behavior of fiber-reinforced polymers from the measured properties and spatial distribution of the different phases and interfaces in the composite. Towards this end, a numerical methodology is proposed herein for the generation of 2D periodic microstructures with arbitrary fiber geometries. A major advantage of the approach presented in this work is the ability of generating high volume fractions of non-circular fibers very efficiently. The underlying algorithm is based on the minimization of fiber overlapping by dynamic translation and rotation of the fibers until intersections are eliminated. The randomness of the microstructures obtained is assessed by means of multiple spatial descriptors.